Computer Based Test: Analysis Of Program Application Selection Of Admission Of New Students In Madrasah Aliyah - Mutia Arianto Putri; Eli Sabrifha; Irawati Irawati; Rini Setyaningsih (At-Tarbiyat, 2022)
This article examines the application of CBT (Computer Based Test) in the selection of new student admissions at MAN Insan Cendekia Siak. The formulation of the problem, namely: 1) How is the application of CBT in the selection of new student admissions. 2) What are the advantages of implementing CBT-based selection of new student admissions compared to PBT. 3) What are the inhibiting factors and alternative problem solving in the selection of new student admissions based on CBT. This article uses a qualitative method with a descriptive approach. The results of the research obtained from the data in the field indicate that: 1) The application of CBT in the PPDB selection is a policy of the Ministry of Religion for superior madrasas. The purpose of implementing CBT is to facilitate the process of accepting new students. 2) The advantages of using CBT compared to PBT are that the test results are more accurate so as to minimize human error, reduce energy, time and costs, the results are immediately known to the participants, the participants are more focused on working on the questions because the exam time is listed, reducing the sales of questions caused by the questions leaks and cheating in conducting test exams, results are more transparent, security is better maintained than exams with paper which causes paper to be damaged or torn. 3) The inhibiting factors for the application of CBT in the PPDB selection are the network is less stable, the website is down, the lights go out and there are still participants who do not understand how to operate computers. How to overcome obstacles, namely: a) network problems, the efforts made by the committee, such as during the socialization, participants are encouraged to bring a modem, then for those who take the exam at home, the committee has previously given an appeal to find a location that has an optimal network. b) for the problem of blackouts, the committee has provided a generator. c) for handling problematic application accounts, the committee will contact the central proktor to login with the participant's password. d) handling for participants who do not understand how to operate a computer, namely the committee provides training to participants before the official test day is held.